ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN HEDGING DENGAN DERIVATIF VALUTA ASING (STUDI PADA PERUSAHAAN NON-FINANSIAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011–2014) - Kussulisty, Maria Josephine Widya Arshita; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2016)
Foreign currency derivatives are commonly used by companies to hedge foreign exchange risk. This study aims to examine the effect of Debt to Equity Ratio (DER), Interest Coverage Ratio (ICR), liquidity, growth opportunity, firm size, foreign debt, and managerial ownership on hedging decision using foreign currency derivatives. Using purposive sampling, 93 non-financial companies listed on the Indonesia Stock Exchange in 2011-2014 are selected as sample. Sample data are collected from annual report published on the Indonesia Stock Exchange website. Logistic regression analysis is used in this study to examine the effect of independent variables on dependent variable. The result of this study proves that ICR, growth opportunity, firm size, and foreign debt have positive and significant effect on hedging decision using foreign currency derivative. Liquidity has negative and significant effect on hedging decision using foreign currency derivatives. Whereas DER and managerial ownership do not influence hedging decision using foreign currency derivatives. The value of Nagelkerke’s R Square is 35,4% which means the variability of the dependent variable that can be explained by the variability of independent variables in the model amounted to 35,4%.